The Effect Of Transformational Leadership Style On Employee Performance In The Population And Civil Registration Service Dairi Regency - Agus Raja Guk guk; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This type of research is a causal associative quantitative research with the aim of analyzing the influence of Transformational Leadership Style on Employee Performance at the Binjai City Regional Secretariat Office. This study was conducted with a population of 68 employees, and the sampling technique used was saturated sampling, where all members of the population were sampled. Data was obtained through questionnaires distributed to all employees from various divisions. The results of the study show that Transformational Leadership Style has a positive and significant effect on Employee Performance. This is evidenced by the t-count value of 9.648 > 1.66827, and the significance value of 0.000 < 0.05. A regression coefficient of 1.197 indicates that every 1 point increase in Transformational Leadership Style will lead to an increase in Employee Performance by 1.197 points, assuming other variables remain constant. The results of the determination coefficient test showed an Adjusted R Square value of 0.579 or 57.9%, which showed that Transformational Leadership Style had a significant influence on Employee Performance, with the remaining 42.1% influenced by other factors that had not been studied in this study. Overall, this study concludes that Transformational Leadership Style can contribute to improving Employee Performance in the Binjai City Regional Secretariat Office.